International human resource management - B. Sebastian Reiche; Anne-Wil Harzing; Helene Tenzer (London : Sage, 2019)
"Used by over 25,000 students across 130 countries, this bestselling text, written by leading international experts in each topic, retains its critical edge, academic rigor and breadth of coverage in the new fifth edition. The new edition reflects the contemporary debates and emerging issues in the field of IHRM, supplementing classic theories and models with recent research and international developments. Divided into three parts, the first section looks at the ways of thinking about IHRM theory and practice; the second section deals with multinational companies and how they manage their workforce around the world; the final section looks at both traditional and newer approaches to IHRM policies and practices. A selection of up-to-date examples from across the globe are used to support the text, including Uber's regulatory challenges across Europe, the gig economy, employment rights after Brexit, health insurance for part-timers in the US and EU, attracting and retaining 'millennials', the world's happiest and unhappiest countries, and CSR in Hong Kong. The book is complemented by free online resources for lecturers and students, including PowerPoint slides, additional case studies, SAGE video clips with critical thinking questions, free SAGE journal articles for every chapter, annotated useful weblinks, and suggested answers to self-assessment questions. Suitable reading for upper-undergraduate and masters level students on IHRM modules"
Keywords: Business and Management